Centro de Investigaciones y Referencia de Aterosclerosis de La Habana, otro eslabón de la salud pública cubana - Fernández-Britto Rodríguez, José Emilio; Armisén Penichet, Alma; Bacallao Gallestey, Jorge; Piñeiro Lamas, Regino; Ferrer Arrocha, Marlene; Alonso Martínez, Maylin; Carballo Martínez, Rosario; Díaz-Perera Fernández, Georgia (Revista Cubana de Salud Pública, 2014)
-